Nursing problems of patients with circulatory failure in the light of Dorothea Orem’s Theory - Koper, Dorota; Senatorski, Grzegorz (Nursing in the 21st Century, 2011)
Nursing problems of patients with circulatory failure in the light of Dorothea Orem’s Theory Circulatory failure (heart failure) is not only important medical, social, economic problem but it is also the nursing problem. The professional nursing requires from the nurse the knowledge and experience. Depending on degree of progression of disease and its course, it requires proper nursing approach. Expression of complexity of this problem facilitates the philosophy of nursing. Dorothea Orem’s Self Care Deficit Theory is optimaltheory of nursing patients with this disease. Aim: Outline of the problems of nursing specific to circulatory failure and an indication at Dorothea Orem’s model as a theory of optimal care of patients with this disease.